Virtual Block Group: A Scalable Blockchain Model with Partial Node Storage and Distributed Hash Table. (8th May 2020) - Yu, Bin; Li, Xiaofeng; Zhao, He
Abstract: The inability to scale is one of the most concerning problems looming in blockchain systems, where every node has to store all contents of the ledger database locally, leading to centralization and higher operation costs. In this paper, we propose a model named virtual block group (VBG), which aims at addressing the node storage scalability problem. Adopting the VBG model, each node only needs to store part of block data and saves the VBG storage index to distributed hash table by taking block data as a resource, thus improving the query efficiency of block data. With the incentive mechanism of block data storage, and the storage verification and audit mechanism of block data, the security and reliability of block data storage can be ensured. The analysis and calculation show that this model saves hard drive storage space of the node to a greater extent with a shorter time of requesting block data, in the premise of ensuring secure and reliable block data. Compared to other technologies such as sharding, our model does not change the consensus mechanism or the network topology and retains the reliability and security of the original blockchain system.